CSIG-37. MERLIN S13 DEPHOSPHORYLATION DRIVES MENINGIOMA WNT SIGNALLING AND CELL PROLIFERATION. (14th November 2022) - Eaton, Charlotte; John Liu, S; Lucas, Calixto-Hope; Casey-Clyde, Tim; Choudhury, Abrar; Daggubati, Vikas; Vasudevan, Harish; Swaney, Danielle; Raleigh, David
Abstract: How Merlin-intact meningiomas arise in the absence of NF2 /Merlin inactivation is incompletely understood. Here, we integrate single-cell RNA sequencing of 86, 000 cells from meningioma xenografts with APEX2 proteomic proximity-labelling mass spectrometry and functional biochemical approaches to discover Merlin Serine 13 (S13) dephosphorylation drives meningioma Wnt signalling and cell proliferation. Cell biology, molecular biology, and biochemical techniques were used to validate Merlin functions in meningioma cells or xenografts using wildtype Merlin constructs or Merlin constructs encoding S13A, phosphomimetic S13D, or cancer-associated missense substitutions (L46R, A211D). Single-cell RNA sequencing of meningioma xenografts showed Merlin rescue activated the Wnt pathway in Merlin-deficient meningiomas. Proteomic proximity-labelling mass spectrometry revealed b-catenin, PKC, and PP1A interactions with wildtype Merlin, but not with Merlin L46R or A211D. b-catenin does not interact with other FERM family members, and Merlin contains a unique N-terminal domain (NTD) with a PKC phosphorylation motif overlapping with a PP1A dephosphorylation motif at S13. Thus, we hypothesized the Merlin S13, PKC, and PP1A may be important for Wnt signalling in Merlin-intact meningiomas. In support of this hypothesis, over-expression of wildtype Merlin or Merlin S13A but not Merlin DNTD, S13D, L46R, A211D, or other FERM family members drove meningioma Wnt signalling and sustained meningioma cell proliferation in vivo . Moreover, b-catenin was detected in proximity to Merlin S13D but not Merlin S13A in meningioma cells. Meningioma cell fractionation and immunofluorescence showed Merlin S13D over-expression stabilized b-catenin at the plasma membrane and inhibited Wnt signalling. Phospho-proteomic mass spectrometry and custom phospho-specific antibodies integrated with shRNA or siRNA gene suppression demonstrated PKC phosphorylated Merlin S13, but meningioma Wnt pathway activation induced PP1A to dephosphorylate Merlin S13 and drive cell proliferation. In summary, Merlin S13 dephosphorylation drives meningioma Wnt signalling and cell proliferation. These data reveal a novel tumor-promoting function of NF2 /Merlin in Merlin-intact meningiomas.